2012
DOI: 10.1128/iai.06370-11
|View full text |Cite
|
Sign up to set email alerts
|

Both Phthiocerol Dimycocerosates and Phenolic Glycolipids Are Required for Virulence of Mycobacterium marinum

Abstract: c Phthiocerol dimycocerosates (PDIMs) and structurally related phenolic glycolipids (PGLs) are complex cell wall lipids unique to pathogenic mycobacteria. While these lipids have been extensively studied in recent years, there are conflicting reports on some aspects of their biosynthesis and on the role of PDIMs and especially PGLs in virulence of Mycobacterium tuberculosis. This has been complicated by the natural deficiency of PGLs in many clinical strains of M. tuberculosis and the frequent loss of PDIMs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
92
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 42 publications
2
92
0
Order By: Relevance
“…PGLs were visualized by spraying the plate with 1% (wt/vol) ␣-naphthol (Acros Organics, Geel, Belgium) prepared in 95% ethanol and 5% sulfuric acid and heating for 5 min (26).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PGLs were visualized by spraying the plate with 1% (wt/vol) ␣-naphthol (Acros Organics, Geel, Belgium) prepared in 95% ethanol and 5% sulfuric acid and heating for 5 min (26).…”
Section: Methodsmentioning
confidence: 99%
“…PDIM and PGLs are abundant and complex cell wall-associated lipids that play roles in cell impermeability and virulence in pathogenic mycobacteria (23)(24)(25)(26)(27). The spontaneous and frequent loss of PDIM has been widely reported in the literature during routine laboratory manipulation of Mycobacterium tuberculosis, the causative agent of human tuberculosis (20)(21)(22).…”
mentioning
confidence: 99%
“…Aliquots (100 l) were added to 96-well plates with black-walled, clearbottomed wells. Nile red or ethidium bromide was added to cells, and fluorescence was measured as described previously (24).…”
Section: Enzymes and Reagentsmentioning
confidence: 99%
“…In pathogenesis, the role of PDIMs of M. tuberculosis was recognized by the studies that identifi ed that mutants of M. tuberculosis were unable to either produce or properly localize PDIMs to the cell envelopeand that demonstrated that PDIM-defi cient strains were attenuated in animal models of infection ( 8,11,(13)(14)(15)(16)(17). Recently, M. tuberculosis and its close pathogenic relative M. marinum were reported to manipulate macrophage recruitment through coordinated use of membrane PDIM and PGLs to initiate infections ( 18 ).…”
mentioning
confidence: 99%